X-Ray diffraction on large single crystals using a powder diffractometer. Issue 20 (12th July 2016) - Jesche, A.; Fix, M.; Kreyssig, A.; Meier, W. R.; Canfield, P. C.
Abstract : Information on the lattice parameter of single crystals with known crystallographic structure allows for estimations of sample quality and composition. In many cases, it is sufficient to determine one lattice parameter or the lattice spacing along a certain, high-symmetry direction, e.g. in order to determine the composition in a substitution series by taking advantage of Vegard's rule. Here we present a guide to accurate measurements of single crystals with dimensions ranging from 200 m up to several millimetres using a standard powder diffractometer in Bragg–Brentano geometry. The correction of the error introduced by the sample height and the optimisation of the alignment are discussed in detail. In particular for single crystals with a plate-like habit, the described procedure allows for measurement of the lattice spacings normal to the plates with high accuracy on a timescale of minutes.